2011
DOI: 10.3390/ma4081399
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of Chitosan: Material Characterization and in vitro Evaluation via Albumin Adsorption and Pre-Osteoblastic Cell Cultures

Abstract: Degree of deacetylation (DDA) and molecular weight (MW) of chitosans are important to their physical and biological properties. In this study, two chitosans, HS (DDA = 73.3%) and AT (DDA = 76.8%), were deacetylated with 45% sodium hydroxide under nitrogen atmosphere at 80 °C or 90 °C for up to 120 min, to obtain two series of chitosans. The polymers produced were characterized for MW by gel permeation chromatography, DDA by titration and UV-vis methods, and crystallinity, hydrophilicity and thermal stability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(132 citation statements)
references
References 29 publications
6
125
1
Order By: Relevance
“…Deacetylated chitosan was synthesized by 'sodium hydroxide deacetylation of chitosan [12][13][14]. Chitosan, which has a DD of 75-85% (5 g), was reacted with 50% sodium hydroxide solution (50 mL) at a 1:10 (W/V) ratio in a round bottom flask (250 mL) under nitrogen atmosphere for four hours at 100 °C.…”
Section: Preparation Of Deacetylated Chitosan With a Dd Value Of 94%mentioning
confidence: 99%
“…Deacetylated chitosan was synthesized by 'sodium hydroxide deacetylation of chitosan [12][13][14]. Chitosan, which has a DD of 75-85% (5 g), was reacted with 50% sodium hydroxide solution (50 mL) at a 1:10 (W/V) ratio in a round bottom flask (250 mL) under nitrogen atmosphere for four hours at 100 °C.…”
Section: Preparation Of Deacetylated Chitosan With a Dd Value Of 94%mentioning
confidence: 99%
“…15 Different degrees of de-acetylation (DDA) of chitosan is normally obtained by the treatment of chitin with alkali and a higher DDA is obtained by increasing the time and temperature, while the molecular weight (mw) of chitosan is dependent on the initial source of material which could be crap, fungi, shrimp etc. This mw normally decreases in the process to obtain a higher DDA [12]. In this study an 87% product with a mw of 2500 kDa was used as received, while the 70% (mw 145kDA] and 40% (mw 15kDA) were prepared.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the degree of de-acetylation (DDA) and the molecular weight are important parameters which determines many physiochemical and biological properties of chitosans [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the solution was boiled for 2 h after that alkali solution was drained off and washed repeatedly with DI till pH was lowered to normal. Finally, chitosan was further dried at room temperature and stored for further uses [19].…”
Section: Methods 221 Extraction Of Chitosan From Chitinmentioning
confidence: 99%